Bond strength of self-etching adhesives to dentin surface after smear layer removal with ultrasonic brushing - Nattawit Niyomsujarit (2020)
© 2019, Japanese Society for Dental Materials and Devices. All rights reserved. This study determined the micro-shear bond strength (μSBS) of two self-etching adhesives to dentin surface after smear layer removal with a novel ultrasonic brushing method. Ninety-five dentin discs were ground flat with diamond burs and divided into 5 groups; no treatment (control), brushing with a custom-made brush for 10 and 30 s without and with ultrasonic application. The smear layer thickness was evaluated using SEM. The 24 h μSBS of Clearfil SE Bond (CSE) and Clearfil Tri S Bond (CTS) to these dentin surfaces were evaluated. Smear layer thickness decreased significantly from control, brushing without, and brushing with ultrasonic groups, respectively. The μSBS of CSE were higher than CTS in all groups. The μSBS were improved with ultrasonic brushing for 30 s for both adhesives. Ultrasonic brushing is the effective method in mechanical smear layer removal which can improve bond strength of self-etching adhesives to ground dentin.